Deciding Heavy Metal Levels in Soil Based on Various Ecological Information through Artificial Intelligence Modeling - Sari, Murat; Cosgun, Tahir; Yalcin, Ibrahim Ertugrul; Taner, Mahmut; Ozyigit, Ibrahim Ilker (TAYLOR & FRANCIS INC, 2022)
The aim of this paper is to decide on heavy metal levels based on ecological parameters by effectively eliminating common disadvantages such as high cost and serious time-consuming laboratory procedures via an effective artificial intelligence approach. Therefore, this study is hinged on an artificial intelligence technique, ANN, because of its low cost and high accuracy in overcoming the mentioned limitations and obstacles in the determination process of the amounts of elements. The ANNs have thus been employed to determine essential heavy metals, such as Fe, Mn, and Zn depending on Ca, K, and Mg concentrations of soil samples obtained from different altitudes in Mount Ida. To the best knowledge of the authors, this is the first study in the literature in which altitude was considered as a parameter in the prediction of nutrient heavy metals. The computed relative errors are significantly low for each of the considered elements (Fe, Mn, and Zn); and are found to be between 1.0-4.1%, 1.0-4.2%, 1.5-7.1%, respectively, for the training, testing, and holdout data. The findings indicate that the relative errors could still be decreased further by assuming the altitude as a factor variable.
Keywords: NEURAL-NETWORK; PREDICTION; QUALITY; WATER; GROUNDWATER; MANAGEMENT; ANN; Computer Science; Engineering